THE MICROBIOTA–GUT–BRAIN AXIS IN MENTAL HEALTH: MECHANISMS, CLINICAL EVIDENCE, AND EMERGING THERAPEUTIC STRATEGIES - Mariusz Suchcicki; Karol Krupiniewicz; Marta Brzęcka; Stanisław Rogiński; Antoni Liebert; Natalia Kmiecik; Kamil Sobolewski; Amadeusz Furmanek; Marek Wojciechowicz; Miłosz Rogiński; Martyna Susek (International Journal of Innovative Technologies in Social Science, 2026)
Interactions between intestinal microbiota and the central nervous system have become one of the most dynamic areas of biomedical research. Accumulating evidence demonstrates that gut microorganisms influence emotional regulation, cognition, and stress responsiveness through complex neural, immune, and metabolic pathways. This review provides an extensive overview of current knowledge regarding the microbiota–gut–brain axis, with particular emphasis on depression and anxiety disorders. Mechanistic insights, human clinical trials, and therapeutic perspectives including probiotics, prebiotics, dietary modulation, and fecal microbiota transplantation are discussed. Despite promising findings, important methodological limitations remain, and further research is required to translate microbiota-based interventions into routine psychiatric practice.